POLYMORPHISMS IN THE ACE2 AND IL-6 GENES AND THEIR POTENTIAL IMPACT ON THE SUSCEPTIBILITY OF SEVERE COVID-19 AMONG ERBIL HOSPITALIZED PATIENTS: Polymorphisms in the ACE2 and IL-6 genes and COVID-19 - Saeed, Khlood N.; Shnawa, Bushra H.; Al-Badran, Adnan I. (Science Journal of University of Zakho, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) is a transmissible illness caused worldwide pandemic. This virus invades host cells via receptors of angiotensin-converting enzyme 2 (ACE2). Moreover, the viral infection stimulates the production of a variety of cytokines like interleukin-6 (IL-6). The main aim of this work is to investigate the connection between COVID-19 and polymorphism of ACE2 (rs2106809 and rs2285666) and IL-6 (-174 G/C) (rs1800795) genes in a group of patients. Genomic DNA was prepared from the peripheral blood of 60 hospitalized patients and 22 controls, the ACE2 and IL-6 genes were amplified by PCR, and the products were sequenced. The data demonstrated a significant variation in the genotype frequency of ACE2 between COVID-19 patients and healthy subjects.The ACE2 (rs2106809) polymorphism outcomes expressed the frequency of three genotypes (TT, TC, and CC), the patients with the TC allele are at risk of developing the disease by approximately 8-folds (OR= 7.5) compared to those with TT and CC alleles. Furthermore, no significant association was found between ACE2 (rs2285666) polymorphism and the risk of developing SARS-CoV-2 which showed a frequency of (AA, AG, and GG) alleles. Additionally, there was no noticeable linkage between the (GG, CC, and CG) genotypes of IL-6 (−174 G/C) (rs1800795) and the hazard of contracting COVID-19. In conclusion, this investigation confirmed that the TC genotype of ACE2 (rs2106809) polymorphism represents a risk factor for acquiring COVID-19 and proposed to perform a critical action in the severity of pathogenicity in Iraqi Kurdish people.